Efeito do potencial de óxido-redução na biolixiviação da calcopirita - Santos, Ana Laura Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Natural sources of sulfide ores come depleting rapidly due to the demand for metal goods industries in production and consumption. Copper is a metal of greater economic interest. About 70% of this metal is found in nature in the form of chalcopyrite (CuFeS2), however it is the mineral that present a major limitations in its extraction. One of the extraction processes is bioleaching, which uses microorganisms capable of promoting the solubilization of metals by metal sulfides oxidation and presents advantages over the common techniques used, mainly for economic and environmental nature. In this context, the present work was carrying out to evaluate the influence of the redox potential in the solubilization of copper from chalcopyrite. For this, ferrous ions oxidation tests were conducted in the presence and absence of the mineral. The bacterium used in the tests was Acidithiobacillus ferrooxidans - LR, the acidophilic species most studied and most commonly found in mine environments. A sample of chalcopyrite from La Chorrera, Colombia, was analyzed by X-ray diffraction (XRD) and showed the dominant presence of chalcopyrite. Ferrous ions oxidation tests were carried out in shaken flasks at 150 rpm, at 30 ºC using different concentrations of ferrous ions (100, 200, and 300 mmol L-1) in T&K medium. The systems were supplied with 2,5% (w/v) of chalcopyrite and 5% (v/v) of A. ferrooxidans fresh inoculum. At the abiotic conditions, the redox potential achieved 420 mV (Ag|AgCl|KCl(sat)) in all ferrous ions concentrations. Besides, these systems showed the highest copper recovery concentrations, such 73%, 90% and 78%, respectively, after 100 days of testing. However, the bacterial systems showed a low copper recovery, about 17% in a redox potential of 610 mV (Ag|AgCl|KCl(sat)). The solid residues were evaluated by XRD and showed, at abiotic conditions the formation of elemental sulfur, jarositas and a significant decrease in chalcopyrite’s...

As fontes naturais de minérios sulfetados vêm se esgotando rapidamente devido à demanda por metais nas indústrias de bens de produção e de consumo. O cobre é um dos metais de maior interesse econômico. Cerca de 70% deste metal é encontrado na natureza na forma de calcopirita (CuFeS2), contudo é o mineral que possui maiores limitações em sua extração. Dentre os processos de extração têm-se a biolixiviação, que utiliza micro-organismos capazes de promoverem a solubilização de metais pela oxidação de sulfetos metálicos, apresentando vantagens em relação às técnicas já utilizadas, principalmente de cunho econômico e ambiental. Neste contexto, o presente trabalho foi desenvolvido com o objetivo de avaliar a influência do potencial de óxido-redução na solubilização de cobre a partir da calcopirita. Para isso, foram realizados ensaios de oxidação de íons ferrosos na presença e ausência do mineral. A bactéria utilizada nos ensaios foi a Acidithiobacillus ferrooxidans - LR, espécie acidófila mais estudada e mais encontrada em ambientes de mina. A amostra de calcopirita, proveniente da localidade de La Chorrera, na Colômbia, foi analisada por difração de raios-X (DRX) e evidenciou a presença dominante de calcopirita. Os ensaios de oxidação foram realizados em frascos, agitados a 150 rpm, a 30ºC sob diferentes concentrações de íons ferrosos (100, 200 e 300 mmol L-1) em meio T&K. Aos sistemas foram adicionados 2,5% (m/v) de calcopirita e 5% (v/v) do inóculo fresco de A. ferrooxidans. Nas condições abióticas, em todas as concentrações de Fe2+, o potencial redox atingiu, em média, 420 mV (Ag|AgCl|KCl(sat)), e foram os sistemas que apresentaram as maiores porcentagens de recuperação de cobre, sendo elas 73%, 90% e 78%, respectivamente, após 100 dias de ensaio. Contudo, os sistemas que continham bactéria apresentaram uma recuperação ínfima de cobre, chegando a apenas 17%, em um potencial médio...
Keywords: Biotecnologia; Lixiviação bacteriana; Reação de oxidação-redução; Cobre; Bacterial leaching